2010
DOI: 10.1186/1477-7525-8-1
|View full text |Cite
|
Sign up to set email alerts
|

The differential mediating effects of pain and depression on the physical and mental dimension of quality of life in Hong Kong Chinese adults

Abstract: ObjectiveThe impact of pain and depression on health-related quality of life (QoL) is widely investigated, yet the pain-depression interactions on QoL remain unclear. This study aims to examine the pain-depression-QoL mediation link.MethodsPain severity were assessed in a sample of Chinese professional teachers (n = 385). The subjects were also assessed on depressive symptoms and QoL. Regression models were fitted to evaluate the pain-depression-QoL relationships.ResultsAbout 44% of the sample had 3-5 painful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 29 publications
(25 reference statements)
10
69
2
1
Order By: Relevance
“…In the current study, prevalence of Type D Personality was 45%, comparable to the 32%5 and 54%18 rates reported in previous studies of the Type D Personality in AF and higher than the prevalence reported in the general population of between 18% and 39% 21. Previous researchers have identified the Type D Personality as a predictor of suicidal ideation in a variety of populations, independent of demographic or socioeconomic variables22, 23 and independent of cardiovascular comorbidities 22.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the current study, prevalence of Type D Personality was 45%, comparable to the 32%5 and 54%18 rates reported in previous studies of the Type D Personality in AF and higher than the prevalence reported in the general population of between 18% and 39% 21. Previous researchers have identified the Type D Personality as a predictor of suicidal ideation in a variety of populations, independent of demographic or socioeconomic variables22, 23 and independent of cardiovascular comorbidities 22.…”
Section: Discussionsupporting
confidence: 83%
“…The influence of the Type D Personality on cardiovascular disease prevalence and outcomes has been a particular focus of previous research 19, 20, 21. In the current study, prevalence of Type D Personality was 45%, comparable to the 32%5 and 54%18 rates reported in previous studies of the Type D Personality in AF and higher than the prevalence reported in the general population of between 18% and 39% 21.…”
Section: Discussionsupporting
confidence: 71%
“…Given the predominance of BVL patients in our study population, our mean score of 0.47 corroborated these findings. A mean HUI3 score of 0.47 is classified as severe disability by HUI3 criteria28 and corresponds to a similar level of QoL impairment as present in individuals suffering from Parkinson's disease (0.45)29 or untreated osteoarthritis (0.46) 30. Our study suggests that while vestibular loss may be overlooked as a benign chronic condition, it is associated with a pervasive negative impact on health‐related quality of life in older individuals.…”
Section: Discussionmentioning
confidence: 53%
“…The GAD-7 was originally created in English (Spitzer et al 2006) and then translated into Spanish (Garcia-Campayo et al 2010). Response options are on a four-point scale (from 0 = not at all to 3 = nearly every day ), and symptoms are evaluated as they have occurred over the prior two weeks.…”
Section: Methodsmentioning
confidence: 99%